Pelatihan Mengkaji Tafsir Ayat-Ayat Keshalehan Sosial dalam Upaya Penguatan Karakter Masyarakat Muslim di Desa Cisaat Subang Jawa Barat - Sa'dullah, Sa'dullah; Effendi, Muhamad Ridwan; Mushlihin, Mushlihin; Nur Aulia, Rihlah; Wajdi, Firdaus; Hani, Ummu; Risma, Risma (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2023)
The target of this activity is the Muslim community of Cisaat Village, Ciater District, Subang Regency, West Java, to carry out training activities in reviewing the interpretation of social piety verses and relating them to the social life of their community so that their understanding is deeper and more comprehensive, as well as skilled in learning to interpret Qur'anic verses. Evidence of achieving one of the objectives of community service in the environment. This activity is carried out through training activities to read or interpret the verses of the Qur'an about social shaleh so that it can provide the understanding and strengthen the character of the people of Cisaat Village. The results of this activity have been able to be felt by the Muslim community of Cisaat Village, especially in increasing the role of the Cisaat Village community, especially Al-Falah Mosque worshippers, to strengthen their social piety behaviour such as hospitality and politeness since the village was made an Educational Tourism Village.